Digital Signal Processing Using MATLAB - Ioana, C.; Mansour, Ali; Quinquis, A.; Radoi, E. (John Wiley & Sons, 2008)
This book uses MATLAB as a computing tool to explore traditional DSP topics and solve problems. this greatly expands the range and complexity of problems that can effectively be studied in signal processing. A large number of worked examples, computer simulations and applications are provided, along with theoretical aspects that are essential in order to gain a good understanding of the main topics. Practicing engineers will also find it useful as an introductory yet highly practical treatment of the subject.